2017
DOI: 10.17533/udea.acbi.14291
|View full text |Cite
|
Sign up to set email alerts
|

Ausencia de efecto citotóxico, mutagénico y genotóxico de extracto acuoso y aceite esencial de <i>Carica candamarcensis</i>. hook. (Plantae: Caricaceae)

Abstract: El extracto acuoso y el aceite esencial de la pulpa de frutos maduros de Carica candamarcensis Hook. f. (1875) (chilacuán, papayuela de clima frío) presentan actividad in vitro anti-Helicobacter pylori, por lo cual se consideran promisorios para realizar una terapia complementaria para controlar la infección gástrica por esta bacteria. El presente trabajo contribuye a profundizar en el estudio de estos extractos evaluando: a) citotoxicidad mediante análisis de viabilidad de linfocitos humanos aislados por el m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…candamarcensis is a plant native to the Andes that is characterized by its therapeutic properties, which is why it is used traditionally to treat burns, flu, gastritis, among other pathologies (Vidal et al, 2009). In addition, studies carried out by Mena-Huertas et al (2011), Ralph et al (2014), and Tonaco et al (2018, suggest that this plant has a therapeutic potential. Previous evidence by Ralph et al (2014), also revealed an anti-inflammatory potential of the P1G10 fraction of the latex of C. candamarcensis in murine models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…candamarcensis is a plant native to the Andes that is characterized by its therapeutic properties, which is why it is used traditionally to treat burns, flu, gastritis, among other pathologies (Vidal et al, 2009). In addition, studies carried out by Mena-Huertas et al (2011), Ralph et al (2014), and Tonaco et al (2018, suggest that this plant has a therapeutic potential. Previous evidence by Ralph et al (2014), also revealed an anti-inflammatory potential of the P1G10 fraction of the latex of C. candamarcensis in murine models.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies carried out with C. candamarcensis have shown in vitro bactericidal activity without having noticeable mutagenic, genotoxic or cytotoxic effects on eukaryotic cells (Mena-Huertas et al, 2011). Mello et al (2008), revealed that enzymes from the P1G10 proteolytic fraction of the fruit exert a protective and reconstructive role in gastric tissue, which is mediated by an increase in mucus content and a stimulation of mitosis to recover gastric ulcer lesions.…”
Section: Introductionmentioning
confidence: 99%